logo
In [1]:
import proveit
from proveit import A, B
from proveit import defaults
from proveit.logic.booleans.conjunction import false_and_false_negated
theory = proveit.Theory() # the theorem's theory
In [2]:
%proving nand_if_neither
With these allowed/disallowed theorem/theory presumptions (e.g., to avoid circular dependencies), we begin our proof of
nand_if_neither:
(see dependencies)
nand_if_neither may now be readily provable (assuming required theorems are usable).  Simply execute "%qed".
In [3]:
defaults.assumptions = nand_if_neither.all_conditions()
defaults.assumptions:
In [4]:
AeqF = A.evaluation()
AeqF:  ⊢  
In [5]:
BeqF = B.evaluation()
BeqF:  ⊢  
In [6]:
false_and_false_negated
In [7]:
n_aand_t = AeqF.sub_left_side_into(
    false_and_false_negated.inner_expr().operand.operands[0],
    auto_simplify=False)
n_aand_t:  ⊢  
In [8]:
BeqF.sub_left_side_into(n_aand_t, auto_simplify=False)
In [9]:
%qed
proveit.logic.booleans.conjunction.nand_if_neither has been proven.
Out[9]:
 step typerequirementsstatement
0generalization1  ⊢  
1instantiation4, 2, 3,  ⊢  
  : , :
2instantiation4, 5, 6  ⊢  
  : , :
3assumption  ⊢  
4theorem  ⊢  
 proveit.logic.equality.substitute_falsehood
5theorem  ⊢  
 proveit.logic.booleans.conjunction.false_and_false_negated
6assumption  ⊢